Topical mitomycin C treatment in corneal and conjunctival intraepithelial neoplasia: A case report - Keleş Şahin, Asena; Uzun, Aslıhan; Erdem, Havva (Journal of Surgery and Medicine, 2021)
Corneal and conjunctival intraepithelial neoplasia is a slowly progressive ocular surface lesion with low malignant potential. Owing to the high recurrence rates, cryotherapy or topical chemotherapy is used with surgical treatment. In this paper, we report the histopathologic findings and treatment of a case of intraepithelial neoplasia that began in the conjunctiva and progressed to the cornea. A 75-year-old woman presented with complaints of redness, irritation and lacrimation in her left eye for around 1 month. Slit-lamp examination revealed a papilliform mass on the nasal conjunctiva along with involvement of the adjacent corneal epithelium. Conjunctival excisional biopsy showed a moderate epithelial dysplasia. Topical 0.04% mitomycin C was administered 4 times daily for 3 weeks. No recurrence was observed in the following 18 months.